2003
DOI: 10.1063/1.1559939
|View full text |Cite
|
Sign up to set email alerts
|

Possible origin of ferromagnetism in (Ga,Mn)N

Abstract: Articles you may be interested inAbove room-temperature ferromagnetism of Mn delta-doped GaN nanorods Appl. Phys. Lett.Ferromagnetic behavior of GaN doped with Mn (Ga 1Ϫz Mn z N) grown by the ammonothermal and chemical transport methods is discussed in terms of a second phase ͑ferromagnetic one͒ produced during the growth process. The reference manganese nitride samples grown by the same method as ͑Ga,Mn͒N reveal room-temperature ferromagnetic behavior, depending on the growth details. Different Mn x N y phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 22 publications
5
72
0
Order By: Relevance
“…Antiferromagnetic GaMn 3 N precipitates have previously been observed in Wurtzite (Ga,Mn)N at high Mn concentrations [16]. Although Mn 4 N phases are not usually identified in MBE-grown (Ga,Mn)N, this is a known room temperature ferromagnet, and undetected inclusions of this or other magnetic secondary phases may be responsible for the room temperature ferromagnetic properties observed here as well as elsewhere [17]. For the (Ga,Mn)N (002) reflection, no significant shift in the peak position on varying the Mn concentration between zero and 10% can be resolved, due to the large width of the 002 reflection.…”
Section: Growth and Structurementioning
confidence: 77%
See 1 more Smart Citation
“…Antiferromagnetic GaMn 3 N precipitates have previously been observed in Wurtzite (Ga,Mn)N at high Mn concentrations [16]. Although Mn 4 N phases are not usually identified in MBE-grown (Ga,Mn)N, this is a known room temperature ferromagnet, and undetected inclusions of this or other magnetic secondary phases may be responsible for the room temperature ferromagnetic properties observed here as well as elsewhere [17]. For the (Ga,Mn)N (002) reflection, no significant shift in the peak position on varying the Mn concentration between zero and 10% can be resolved, due to the large width of the 002 reflection.…”
Section: Growth and Structurementioning
confidence: 77%
“…Comparing the measured room temperature ferromagnetism to the Mn concentration measured by SIMS, we obtain a magnetic moment of only around 0.1 µ B / Mn, indicating that most of the Mn in the sample is not contributing to the room temperature coupling. The origin of this signal is not presently known, however it has been noted that there are several Mn x N y phases which have a ferromagnetic transition temperature above room temperature [17], which could account for the observed behaviour. Here we take the view that, in order to 6 understand the magnetic properties of (Ga,Mn)N, it is important to study the system as a whole rather than concentrating only on the small room temperature ferromagnetic part (we note however that the opposite approach is frequently taken in the experimental literature surrounding (Ga,Mn)N).…”
Section: Magnetic Propertiesmentioning
confidence: 96%
“…It has been theoretically and experimentally suggested that the Mn level is too deep in the GaN band gap to be an effective acceptor [7][8][9], explaining why ptype conduction is not generally observed. Therefore, the reported ferromagnetism has been ascribed to undetected metallic secondary phases [11,12].…”
Section: School Of Physics and Astronomy University Of Nottingham Nmentioning
confidence: 99%
“…In some parts ( suggests the presence of ferromagnetic precipitations in our crystals. Such situation is commonly found in GaN--based DMS [9]. Detailed analysis of the M (B) data allows a reasonable subtraction of the FM phase contribution [1].…”
Section: Resultsmentioning
confidence: 99%